2015
DOI: 10.3109/14017431.2015.1009383
|View full text |Cite
|
Sign up to set email alerts
|

Focused ultrasound of the pleural cavities and the pericardium by nurses after cardiac surgery

Abstract: Objectives. We aimed to study the feasibility and reliability of focused ultrasound (US) examinations to quantify pericardial (PE)- and pleural effusion (PLE) by a pocket-size imaging device (PSID) performed by nurses in patients early after cardiac surgery. Design. After a 3-month training period, with cardiologists as supervisors, two nurses examined 59 patients (20 women) with US using a PSID at a median of 5 days after cardiac surgery. The amount of PE and PLE was classified in four categories by US (both)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 24 publications
3
37
1
16
Order By: Relevance
“…20 Point-of-care ultrasound of the pleural cavities is a sensitive and specific test for detection of PLE, 1 21 and is previously shown to be superior to chest X-ray for diagnostics of PLE. 22 The current study indicates that caring for improvement of patient-reported outcomes is an additional reason for systematic use of ultrasound to assess PLE in patients with HF, 21 as excessive volume status could be an explanation for the poor QoL. However, if the availability of ultrasound is limited, a MLHFQ-score >40 identifies ∼80% of those with moderate to severe PLE and these should be referred to ultrasound.…”
Section: Discussionmentioning
confidence: 82%
“…20 Point-of-care ultrasound of the pleural cavities is a sensitive and specific test for detection of PLE, 1 21 and is previously shown to be superior to chest X-ray for diagnostics of PLE. 22 The current study indicates that caring for improvement of patient-reported outcomes is an additional reason for systematic use of ultrasound to assess PLE in patients with HF, 21 as excessive volume status could be an explanation for the poor QoL. However, if the availability of ultrasound is limited, a MLHFQ-score >40 identifies ∼80% of those with moderate to severe PLE and these should be referred to ultrasound.…”
Section: Discussionmentioning
confidence: 82%
“…The 25 selected studies were published between 2009 and 2017. Fourteen studies were European ( 9 , 10 , 11 , 12 , 13 , 14 , 15 ) (seven from Norway ( 16 , 17 , 18 , 19 , 20 , 21 , 22 )), five from Japan ( 23 , 24 , 25 , 26 , 27 ), five from USA ( 28 , 29 , 30 , 31 , 32 ) and one from India ( 33 ). We considered the findings in three groups: (1) scans performed by experienced users ( n = 16); (2) scans performed by non-expert physicians, with little or no prior experience ( n = 7); (3) scans performed by nurses with variable experience ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…Different applications of pocket-size devices have been recently introduced, particularly in the setting of ED and critical care units. [9][10][11][12][13] In outpatients setting the use of pocket-size devices have demonstrated its usefulness when used by doctors, nurses, and medical students. 14 In low resources settings, the use of small devices is time saving and has demonstrated its clinical applications and impact on patients' management.…”
Section: Its Principalmentioning
confidence: 99%
“…The ability of combining small size with high‐resolution imaging has led to a widespread use of small apparatus. Different applications of pocket‐size devices have been recently introduced, particularly in the setting of ED and critical care units . In outpatients setting the use of pocket‐size devices have demonstrated its usefulness when used by doctors, nurses, and medical students .…”
Section: Introductionmentioning
confidence: 99%